THE COLLABORATIVE RELATIONAL DIAGNOSIS - Alfredo Rojas (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2018)
In the practice of Social Work, the traditional concept of diagnosis refers to a simple formula: a professional with a certain competence linked to knowing and doing, issues a judgment in which the nature and magnitude of the difficulties have been synthesized and interpreted -needs of a person, family, group or community. This vision does not incorporate the relational and cooperative dimension of the encounter between the professional and the person in the framework of a helping relationship. From second order cybernetics, that of observing systems, what professionals believe, think and value (as professionals and as people), influences the vision that we are going to build of the person / family. If subjectivity occurs, what prevents the assessment of the problem situation from being able to co-construct it collaboratively between the professional and their clients? From this perspective, we can speak of collaborative diagnosis. The work collects the results of the practical application, under experimental conditions and in the daily practice of professionals, of the criteria to develop a co-diagnosis. It is useful to guide conversations with clients and is open to the adjustments that each relationship needs in its context.